2021
DOI: 10.1016/j.euo.2020.12.010
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a Novel Risk Score to Select the Optimal Candidate for Cytoreductive Nephrectomy Among Patients with Metastatic Renal Cell Carcinoma. Results from a Multi-institutional Registry (REMARCC)

Abstract: Background: Selection of patients for upfront cytoreductive nephrectomy (CN) in metastatic renal cell carcinoma (mRCC) has to be improved. Objective: To evaluate a new scoring system for the prediction of overall mortality (OM) in mRCC patients undergoing CN. Design, setting, and participants: We identified a total of 519 patients with synchronous mRCC undergoing CN between 2005 and 2019 from a multi-institutional registry (Registry for Metastatic RCC [REMARCC]). Outcome measurements and statistical analysis: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…They identified six poor prognostic factors: ≤30 body mass index, lung metastasis, liver metastasis, bone metastasis, >3 metastatic lesions, and <80 KPS. 46 We conducted external validation of the REMARCC classification and showed that IPTW-adjusted OS with CN was longer with CN than without CN with a low score (0-2 factors; HR 0.36; 95% CI 0.25-0.53), whereas it was similar with intermediate and high scores (3-6 factors; HR 0.91; 95% CI 0.54-1.54). 47 Briefly, previous retrospective studies in the TT era inferred that immediate CN may be considered for patients who can expect long-term survival (Fig.…”
Section: Immediate Cn (Table 1)mentioning
confidence: 98%
See 1 more Smart Citation
“…They identified six poor prognostic factors: ≤30 body mass index, lung metastasis, liver metastasis, bone metastasis, >3 metastatic lesions, and <80 KPS. 46 We conducted external validation of the REMARCC classification and showed that IPTW-adjusted OS with CN was longer with CN than without CN with a low score (0-2 factors; HR 0.36; 95% CI 0.25-0.53), whereas it was similar with intermediate and high scores (3-6 factors; HR 0.91; 95% CI 0.54-1.54). 47 Briefly, previous retrospective studies in the TT era inferred that immediate CN may be considered for patients who can expect long-term survival (Fig.…”
Section: Immediate Cn (Table 1)mentioning
confidence: 98%
“…The European Association of Urology Young Academic Urologist Kidney Cancer group developed the REMARCC classification using 519 synchronous mRCC patients undergoing CN. They identified six poor prognostic factors: ≤30 body mass index, lung metastasis, liver metastasis, bone metastasis, >3 metastatic lesions, and <80 KPS 46 . We conducted external validation of the REMARCC classification and showed that IPTW‐adjusted OS with CN was longer with CN than without CN with a low score (0–2 factors; HR 0.36; 95% CI 0.25–0.53), whereas it was similar with intermediate and high scores (3–6 factors; HR 0.91; 95% CI 0.54–1.54) 47 .…”
Section: Immediate Cn (Table 1)mentioning
confidence: 99%
“…A result from the multi-institutional registry (REMARCC) showed that different metastatic sites had different effects on the survival benefits of patients with mRCC. The survival rate of patients with distant metastasis were often worse ( 33 ). Similar to their study, we found that patients with distant metastasis were often apt to early death, especially those with liver and brain metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though numerous prognostic scales have been developed for this purpose during the cytokine era, external validation has shown that they all perform poorly in a targeted therapy-predominant cohort [62]. For this reason, newer scales have been developed during the targeted therapy era; examples include those by McIntosh et al [67] and Marchioni et al [68]. However, these remain to be prospectively evaluated and externally validated before they can be implemented into routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%